RETRACTED: Enhancing college English teaching models through the application of cognitive psychology: a focus on listening processes - Gui, Tianjiao; Wu, Chenmeng (Frontiers in Education, 2023)
The uneven English proficiency level among college students can lead to a lack of confidence and a passive learning process, especially for those with weak foundations. However, applying cognitive psychology principles in college English teaching can optimize the teaching mode and create a high-quality classroom atmosphere. By stimulating students' enthusiasm through practical activities, respecting and encouraging their learning, teachers can improve the quality of teaching. This empirical study offers a comprehensive exploration of the relevance of cognitive psychology in college English teaching. It discusses the challenges faced by college students in learning English due to uneven proficiency levels and passive attitudes towards learning. The paper also introduces innovative teaching models and strategies that can optimize the learning experience and improve teaching quality. By addressing these challenges and providing effective solutions, the paper aims to enhance students' English proficiency and overall learning outcomes. The implementation of cognitive psychology in English teaching is expected to create a positive classroom atmosphere, promote student engagement and motivation, and ultimately lead to continued improvement in the students' English level.